2020
DOI: 10.1088/1757-899x/991/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Kaffir Lime (Citrus hystrix DC.) essential oil by steam distillation and evaluation of chemical constituents

Abstract: Citrus hystrix which is commonly known as Kaffir Lime, is a plant with great potential for research and commercialization. C. hystrix essential oil is used as a fragrance to increase appetite in food, or sweet-smelling in cosmetics and antibacterial properties in the health field. Most research have focused on the peels, yet the EO content in C. hystrix leaves is also noteworthy. There are many essential oils extraction methods from conventional to advanced techniques. However, it is necessary to consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The plant materials were air-dried and cut into small pieces prior to the extraction of the essential oil. These fresh plant materials were subjected to microwave-assisted extraction using a NEOS Milestone appliance for 90 minutes under the power of 900 W (yields an extract temperature of 100-110°C) [17,18]. The resulting volatile oils were stored in amber vials and refrigerated at 4°C until analysis.…”
Section: Extraction Of Essential Oilsmentioning
confidence: 99%
“…The plant materials were air-dried and cut into small pieces prior to the extraction of the essential oil. These fresh plant materials were subjected to microwave-assisted extraction using a NEOS Milestone appliance for 90 minutes under the power of 900 W (yields an extract temperature of 100-110°C) [17,18]. The resulting volatile oils were stored in amber vials and refrigerated at 4°C until analysis.…”
Section: Extraction Of Essential Oilsmentioning
confidence: 99%
“…They were analyzed for UV-Visible spectrum to select the best solvent. Peel of C. hystrix is extracted through the process of steam distillation until obtaining essential oil [15]. Then, essential oil nanocapsule were prepared by mixing essential oil, chitosan (Ch) in 1 % CH3COOH and SDS, surfactant in various ratios, as the Table 1 below.…”
Section: Preparation Of Herbalmentioning
confidence: 99%
“…Citrus essential oil has a pleasant aroma, high levels of Limonene and is widely used in foods and cosmetics [1][2][3][4][5]. Recent studies have also shown that Limonene also dissolve stones, and destroy tumors so it can be used in medicine [6][7][8][9][10][11]. In Vietnam, especially in the Mekong River Delta, including Dong Thap province, another species of Citrus in the Rutaceae family (orange family) is kink, the common is Citrus japonica Thunb.…”
Section: Introductionmentioning
confidence: 99%